Physical Education in 1956 (Fiep Bulletin - online, 2015)
Physical education must lead the individual to an improvement of his figure (morphology) and of his efficiency (functional and psychoactive education), whilst taking note of a large number of factors such as heredity, milieu, climate, etc.